Factors related to Internet and game addiction among adolescents: A scoping review - Siripattra Juthamanee; Joko Gunawan (Belitung Nursing Journal, 2021)
Background: Understanding factors influencing Internet and game addiction in children and adolescents is very important to prevent negative consequences; however, the existing factors in the literature remain inconclusive.Objective: This study aims to systematically map the existing literature of factors related to Internet and game addiction in adolescents.Methods: A scoping review was completed using three databases - Science Direct, PROQUEST Dissertations and Theses, and Google Scholar, which covered the years between 2009 to July 2020. Quality appraisal and data extraction were presented. A content analysis was used to synthesize the results.Results: Ultimately, 62 studies met inclusion criteria. There were 82 associated factors identified and grouped into 11 categories, including (1) socio-demographic characteristics, (2) parental and family factors, (3) device ownership, Internet access and location, social media, and the game itself, (4) personality/traits, psychopathology factors, self-efficacy, (5) education and school factors, (6) perceived enjoyment, (7) perceived benefits, (8) health-compromising behaviors, (9) peers/friends relationships and supports, (10) life dissatisfaction and stress, and (11) cybersafety.Conclusion: Internet and game addiction among adolescents are multifactorial. Nurses should consider the factors identified in this study to provide strategies to prevent and reduce addiction in adolescents.